A Comparative Study on the Role of Negative Behaviors of Organizational Behavior in inefficient Occupational Behaviors of Employees - Ali Yasini; Ardeshir Shiri; Fariba Moradi Kia (مطالعات مدیریت بهبود و تحول, 2018)
The present research is to provide an explaining model for employee inefficient behaviors based on Managers abusive supervision.  This study is practical in terms of purpose and data collection method is descriptive-correlational. The statistical population consists managers and employees of Ilam  public organizations, about 5000 people among whom 360 individuals were selected randomly as a sample by using Krejcie and Morgan's table (1995). The data collection tool was a standard questionnaire of which their reliability is measured through Cronbach’s alpha as well as their validity by constructive validity. The data was processed using SPSS software and visual-pls in order to determine the validity of the hypotheses and the significance level of the relationships between the variables. The findings of this research show that the Managers abusive supervision has a significant effect on inefficient job behaviors. The findings of this study show that perceived Abusive supervision has a positive and meaningful effect on the two variables of neurotic behavior and emotional exhaustion of which its effect’s coefficient on neurotic behavior(β = 0.55) is more than emotional exhaustion(β = 0.35). Also there is a negative and inverse influence on perceived Abusive supervision of employees' Prosocial reaction (β =-0.390). Neurotic behavior has a positive and significant effect on the two variables of organizational obstruction and ineffective Counterproductive work behavior of which its effect’s coefficient on organizational obstruction(β = 517) is more than inefficient Counterproductive work behavior(β = 0.367). The effect of neurotic behavior on Prosocial reaction(β = 0.077) has been statistically excluded and has no significant effect. Findings show that emotional exhaustion has a positive and significant effect on organizational obstruction as well as the inefficient Counterproductive work behavior variables, which has a significant effect on organizational obstruction(β = 0.398) than ineffective occupation behaviors(β = 0.221). The emotional exhaustion has a negative and inverse effect on Prosocial reaction(β= -0.285). Organizational obstruction has a positive and significant effect on inefficient job behaviors (β= 0.214). Also Prosocial reaction has a negative and significant effect on organizational obstruction(β = -0.653).